Bibliometric Analysis of Inclusive Tourism Communication Research in Indonesia 2014-2024 in an Effort to Explore Opportunities and Determine Development Directions - Ramadhanty, Ghina; Novianti, Evi; Khadijah, Ute Lies Siti (Borong Newinera Publisher, 2025)
This study aims to analyze the development of research on inclusive tourism communication in Indonesia over the past decade (2014–2024) using a bibliometric approach. Data were obtained from the Scopus database using the keywords